Estudo histológico e propagação assexuada de genótipos de lavanda - Menegusso , Fernanda Jaqueline (2021)
The aim of this study was to evaluate the rooting potential of lavender cuttings as a function of species, genotype, indolbutyric acid (IBA) concentration and its mode of application and essential oil quality. Three experiments and one essential oil characterization were conducted. Experiment 1: The experiment was carried out from March to April 2019 under greenhouse conditions with 50% shading, in the Experimental Station of Horticulture and Protected Cultivation of Unioeste, Campus Marechal Cândido Rondon (PR). Branches were collected from the mother plants with the aid of pruning scissors, cultivated in an experimental area of the same university. The experimental design was in randomized blocks, in a 2 x 4 factorial scheme [species L. angustifolia and L. canariensis x concentrations of 0, 1000, 2000 and 3000 mg L-1 of IBA. Experiments 2 and 3: Experiments carried out from October to December 2019 at the “Centro de Investigaciones de Albaladejito” in Cuenca, Cuenca, Spain. Experiment 2 had 3 genotypes (G621, G763 and G764) x 4 IBA concentrations (0, 1000, 2000, 3000 mg L-1) and experiment 3 with the same genotypes x types of immersion (slow and fast). In experiments 1, 2 and 3, the phytotechnical parameters, percentage of rooted and callused cuttings, number of roots and length of the longest root (cm) were evaluated. For experiments 1 and 2, anatomical analyzes were performed, focusing on the formation of adventitious roots. The characterization of essential oil of the species L. canariensis, L. latifolia and L. dentata was also carried out. For experiment 1 it was found that for the parameters calloused cuttings and root length there was significance only for L. angustifolia species, with a lower percentage of calloused cuttings and longer root length. Rooting and number of roots increased proportionally to the increase in IBA concentration. In the histological study, the species L. latifolia presented an essentially secondary structure and L. canariensis presented an essentially primary structure. In L. latifolia there are isolated fiber bundles in the cortical region and in L. canariensis there are well-developed trichomes and fiber bundles over the phloem. For both species under study there was a correlation between this study and the xi phytotechnical evaluation of the number of roots. It is concluded that the use of IBA for the species under study is indicated at the highest dose tested (3000 mg L-1) and the presence of these fiber bundles does not prevent root emergence. In experiment 2, it was found that AIB promoted an increase in rooting, with the exception of the G764 genotype. For number of roots only the concentrations of IBA were significant, showing a decrease in values with the increase of IBA. In the histological study, fiber bundles forming a discontinuous cylinder can be observed in the analyzed genotypes, such as in the stem of genotype 621. Regarding immersion (experiment 3), G621 showed greater root length in fast immersion and G764 in slow immersion. An average concentration of 1500 mg L-1 of IBA is recommended for genotypes G621 and G763 and 400 mg L-1 for G764. Despite the presence of fiber bundles, there is no impediment to the emission of adventitious roots in the studied genotypes. Fast immersion was favorable for G621 and slow for the G764 genotype. In the characterization of the oil, it was found that sample B (L. canariensis) differed from the others in terms of chemical group and major components, having peculiar characteristics that can be used. It is concluded that there are differences between lavender species and genotypes regarding rooting and the existing fiber bundles do not prevent rooting. however, anatomical barriers are not visualized for the species under study. Essential oil also has different characteristics between species. Between different parts of the same species there are some differences in the amounts of components, however the major groups remain the same. Lavandula canariensis presented interesting chemical characteristics to be commercially exploited.